Penamaan Desa di Kecamatan Tapung Kabupaten Kampar - Della Putri Andini; Melia Anggraeni; Ramaida Ramaida; Siti Samsiah (UIR Press, 2023)
Naming is a symbol process that refers to a referent. Giving a name to each area is not only for designation but to make it easier for someone to recognize the identity of the area. Each area is given a name by the community based on the situation and condition of each area. This study uses etymological and semantic approaches. This study describes: 1) the origin of village naming in Tapung District, Kampar Regency